SEXUALITY AND POWER DYNAMICS: A DISCOURSE ANALYSIS OF TEACHER-STUDENT INTERACTIONAL PATTERN - Nwode, Goodluck Chigbo; Anyadiegwu, Justina C. (EBSU Journal of Social Sciences and Humanities, 2023)
Teacher-student interactional pattern is largely characterised by unhealthy sexuality and power dynamics. With discourse analysis, this study analyses the kind of sexuality and the extent of power dynamics that characterise the pattern of interaction between teachers and students across nations’ colleges and tertiary institutions. It reveals that illegitimate sexual intercourse and relationships between teachers and students arise from the exercise of power on students by most of the teachers involved in the acts. Upon teachers’ power influence, students get compelled into sexual intercourse and sometimes sexual relationships with them. The predominant sexuality teachers and students engage in is heterosexuality. The power dynamics involved in their interaction allows for sexual extortion and suzerainty relationship between teachers and students. The relationship and the discourse between them are less interactive and largely authoritative, exploitative and monopolistic. The study concludes that the asymmetric and rigid power-enveloped interactional pattern of teacher-student relationships paves way for teachers to incessantly breach the rights of students over time. It recommends that symmetrical and loose power interactional pattern should be instituted and unhealthy sexuality and power dynamics should be outlawed. The study is grounded by two theories of integration, with which discourse analysis is integrated with other fields and approaches, as in integrating linguistics with education.